Safety and efficacy of iron chelates of lysine and glutamic acid as feed additive for all animal species. (25th July 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of iron chelates of lysine and glutamic acid (Iron‐LG) as nutritional feed additive for all animal species. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) Panel concludes that, owing to safety considerations, Iron‐LG should not be used in water for drinking. Iron‐LG is safe for chickens for fattening; this conclusion can be extrapolated to all animal species/categories provided that the maximum authorised levels in the EU for total iron in feed are not exceeded. No increases in the iron content of animal tissues and products are expected from the use of Iron‐LG in animal nutrition. There is no indication that the toxicity of Iron‐LG is essentially different from that described for inorganic divalent iron. The use of Iron‐LG in animal nutrition is of no concern for consumer safety provided that the maximum authorised total iron levels in feed are respected. Owing to the iron and nickel content of Iron‐LG, the handling of the additive, poses a risk to users by inhalation. The additive is considered as a skin and respiratory sensitizer; it is irritant to eye and non‐irritant to skin. Iron‐LG is intended to be a substitute for other authorised iron additives and will not further increase the environmental burden of iron; therefore, the FEEDAP Panel considers that the use of the additive in animal nutrition would not pose an additional risk for the environment. Owing to the limitations in the study provided, the FEEDAP Panel cannot conclude on the efficacy of the additive for chickens for fattening, and thus, on the efficacy of Iron‐LG to all animal species and categories. The FEEDAP Panel posed a recommendation concerning the description of the additive.